F-ZIF-67 / PDMS composite film, preparation method and application thereof, friction nano-generator and application thereof

By using F-ZIF-67/PDMS composite film as a negative friction material for friction nanometers, the problem of insufficient output performance in existing technology has been solved, and higher power generation efficiency and more stable output performance are achieved. It is suitable for A variety of application scenarios.

CN119331294APending Publication Date: 2025-01-21ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411447022.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing friction nanogenerators have insufficient output performance in large-area cathode protection, and energy collection and energy conversion efficiency need to be improved.

Method used

The F-ZIF-67/PDMS composite film is used as a negative friction material. By mixing ZIF-67 powder with PDMS forehead, ultrasonic dispersion, vacuum, solidification, and fluoride modification, to prepare high-performance friction nano-generators Essence

Benefits of technology

The triboelectrification performance and charge storage capacity of the triboelectric nanogenerator are significantly improved, achieving higher power generation efficiency and more stable output performance, and are suitable for electrochemical cathodic protection, self-powered sensors and wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331294A_ABST
    Figure CN119331294A_ABST
Patent Text Reader

Abstract

The invention provides an F-ZIF-67 / PDMS composite film, a preparation method and application thereof, a friction nano-generator and application thereof. The friction nanometer generator is composed of a positive friction layer, a negative friction layer and electrodes. Wherein the negative friction layer is particularly made of an F-ZIF-67 / PDMS composite film, and the positive friction layer is made of a PTFE material; by introducing the ZIF-67 nanoparticles, the dielectric constant of the composite film is remarkably improved, and the friction polarity of the dielectric layer is influenced by performing fluorination modification on the composite film, so that the charge density and the output performance of the friction nano-generator are improved. The friction nanometer generator can efficiently convert mechanical energy in the environment into electric energy and is successfully applied to an electrochemical cathode protection system, the system shows an excellent anti-corrosion effect on steel materials such as Q235 carbon steel, 304SS and A3 carbon steel, and a new solution is brought to the field of corrosion protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of friction nanogenerators, and in particular to a F-ZIF-67 / PDMS composite film and a preparation method and application thereof, a friction nanogenerator and application thereof. Background Art

[0002] Metal corrosion is a widespread phenomenon in the construction, shipbuilding and automotive industries, and the global losses and disasters caused by it cannot be ignored. Therefore, corrosion protection has become an issue that we urgently need to pay attention to. Among them, cathodic protection, as an efficient anti-corrosion method, has attracted much attention. Traditionally, cathodic protection mainly relies on sacrificial anode cathodic protection and impressed power protection, but both methods require energy support from external equipment. Therefore, seeking reliable energy has become an urgent problem to be solved.

[0003] As an emerging energy technology, the triboelectric nanogenerator can effectively convert tiny mechanical energy into electrical energy, opening up a new path in the field of metal corrosion protection. At present, a cathodic protection system based on triboelectric nanogenerator has been developed, but in order to achieve a large-area cathodic protection effect, its output performance needs to be further improved, including improving energy collection and energy conversion efficiency. Therefore, it is necessary to explore new methods to ensure that TENG (triboelectric nanogenerator) maintains excellent performance and stable output during operation, which is of great significance to the development of triboelectric nanogenerator and corrosion protection.

[0004] In recent years, metal organic frameworks (MOFs) have been widely used in various fields as a multifunctional material. This material is composed of organic ligands connected with metal ions, and has high crystallinity, high specific surface area, unique morphology, adjustable porosity, and high thermal stability and chemical stability. These characteristics make MOFs an ideal choice in the field of TENG devices. However, the current MOFs materials still have the defect of low power generation efficiency as triboelectric layers. Based on this, it is necessary to improve this. Summary of the invention

[0005] In view of this, the present invention provides a F-ZIF-67 / PDMS composite film and a preparation method and application thereof, a friction nanogenerator and application thereof, so as to solve the defects existing in the prior art.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a F-ZIF-67 / PDMS composite film, comprising the following steps:

[0008] Adding ZIF-67 powder to a PDMS precursor, stirring and then ultrasonically dispersing to obtain a mixed solution; the PDMS precursor includes a curing agent and a PDMS matrix;

[0009] The mixed solution was vacuumed to eliminate air bubbles in the solution;

[0010] The vacuumized mixed solution is coated on a substrate and cured to obtain a ZIF-67 / PDMS composite film;

[0011] The ZIF-67 / PDMS composite film is immersed in a fluorosilane solution and dried to obtain a F-ZIF-67 / PDMS composite film.

[0012] Preferably, the fluorosilane solution comprises perfluorodecyltrimethoxysilane and ethanol, and the mass concentration of perfluorodecyltrimethoxysilane in the fluorosilane solution is 1-2%.

[0013] Preferably, the method for preparing the ZIF-67 powder comprises the following steps:

[0014] Dissolve Co(NO3)2 in methanol, then add a methanol solution containing 2-methylimidazole to obtain a mixed solution;

[0015] The mixed solution was stirred, aged, and centrifuged to obtain a precipitate, which was then washed and dried to obtain ZIF-67 powder.

[0016] Preferably, the ultrasonic dispersion time is 30 to 100 minutes;

[0017] And / or, the mass ratio of the curing agent to the PDMS substrate is 1:(10-12);

[0018] And / or, the mass ratio of the ZIF-67 powder to the PDMS precursor is 1:(10-100);

[0019] And / or, the curing time is 1 to 4 hours and the curing temperature is 70 to 90°C.

[0020] Preferably, in the step of immersing the ZIF-67 / PDMS composite film in a fluorosilane solution, the immersion temperature is 20 to 25° C. and the time is 2 to 3 hours;

[0021] And / or, stirring the mixture for 2 to 4 hours, aging, centrifuging to obtain a precipitate, washing it by centrifugation with methanol, and drying it to obtain ZIF-67 powder; wherein the aging temperature is 20 to 25° C., and the aging time is 20 to 30 hours;

[0022] and / or, the mass volume ratio of Co(NO3)2, methanol, and methanol solution containing 2-methylimidazole is (3-4) g: (40-50) mL: (80-100) mL;

[0023] The mass of 2-methylimidazole in the methanol solution containing 2-methylimidazole is 3.5-4.0 g.

[0024] In a second aspect, the present invention further provides a F-ZIF-67 / PDMS composite film, which is prepared by the preparation method.

[0025] In a third aspect, the present invention also provides an application of the F-ZIF-67 / PDMS composite film as a negative friction material in the preparation of a friction nanogenerator.

[0026] In a fourth aspect, the present invention further provides a friction nanogenerator, comprising a first power generation unit and a second power generation unit;

[0027] The first power generation unit includes a first electrode and a negative friction layer located on the surface of the first electrode;

[0028] The second power generation unit includes a second electrode and a positive friction layer located on the surface of the second electrode;

[0029] Wherein, the negative friction layer material is the F-ZIF-67 / PDMS composite film;

[0030] The first electrode is electrically connected to the second electrode.

[0031] Preferably, it further comprises a first substrate and a second substrate;

[0032] The first substrate is attached to the surface of the first electrode away from the negative friction layer;

[0033] The second substrate is attached to the surface of the second electrode away from the positive friction layer;

[0034] The material of the positive friction layer is PTFE.

[0035] In a fifth aspect, the present invention also provides an application of the friction nanogenerator in electrochemical cathodic protection, self-powered sensors and wearable devices.

[0036] The F-ZIF-67 / PDMS composite film and its preparation method and application, friction nanogenerator and application of the present invention have the following beneficial effects compared with the prior art:

[0037] 1. The preparation method of the F-ZIF-67 / PDMS composite film of the present invention is relatively simple. A high-performance F-ZIF-67 / PDMS composite film can be prepared by simple steps of solution mixing, stirring, curing, soaking, etc. This preparation method has the advantages of low cost, simple operation, good repeatability, etc., and is conducive to large-scale production and commercial application;

[0038] 2. ZIF-67, as a metal organic framework (MOF) material, has a rich pore structure and a high specific surface area. Combining it with PDMS can significantly improve the triboelectric performance and charge storage capacity of the film. PDMS itself has good flexibility, biocompatibility and chemical stability. Combining it with ZIF-67 can further enhance the mechanical strength and durability of the material.

[0039] 3. The present invention adopts the method of embedding the metal organic framework into PDMS to improve the dielectric constant, and the chemical properties of the material surface are significantly changed after the ZIF-67 / PDMS film is fluorinated, especially the electronegativity of the material is improved and the surface energy is reduced; and the PTFE material with a large difference in electronegativity is selected as the positive friction material, which greatly increases the number of charges between the friction materials, achieves higher power generation efficiency and more stable output performance, and TENG can also effectively convert mechanical energy into electrical energy, providing a stable and reliable energy supply for low-power electronic devices;

[0040] 4. The friction nanogenerator of the present invention has the advantages of high output efficiency and simple preparation process, which makes the friction nanogenerator of the present invention have broad application prospects and important social significance in the fields of self-powered anti-corrosion, energy collection, environmental monitoring, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0042] Figure 1 It is a schematic structural diagram of the friction nanogenerator of the present invention;

[0043] Figure 2 A schematic diagram of the working principle of the friction nanogenerator of the present invention;

[0044] Figure 3 is a SEM image of the ZIF-67 powder prepared in Example 1 of the present invention;

[0045] Figure 4 is a SEM image of the F-ZIF-67 / PDMS composite film prepared in Example 2 of the present invention;

[0046] Figure 5The XRD patterns of the ZIF-67 powder, pure PDMS, the F-ZIF-67 / PDMS composite film prepared in Example 2, and the ZIF-67 / PDMS composite film prepared in step S3 of Example 2 in the present invention;

[0047] Figure 6 The triboelectric output performance diagram of high-performance triboelectric nanogenerators based on pure PDMS, ZIF-67 / PDMS composite film, and F-ZIF-67 / PDMS composite film;

[0048] Figure 7 This is a rectifier circuit diagram of the friction nanogenerator F-ZIF-67 / PDMS-TENG in Example 3 of the present invention;

[0049] Figure 8 Schematic diagram of the self-powered anti-corrosion system of the friction nanogenerator F-ZIF-67 / PDMS-TENG in Example 3 of the present invention;

[0050] Fig. 9 Schematic diagram of OCP curves with and without TENG coupling;

[0051] Fig.10 Schematic diagram of Tafel curve with and without TENG coupling. DETAILED DESCRIPTION

[0052] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0053] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any quoted numbers (fractions or integers) within the indicated range.

[0055] The present application embodiment provides a method for preparing a F-ZIF-67 / PDMS composite film, comprising the following steps:

[0056] S1, adding ZIF-67 powder to PDMS precursor, stirring and then ultrasonically dispersing to obtain a mixed solution; the PDMS precursor includes a curing agent and a PDMS matrix;

[0057] S2, vacuuming the mixed solution to eliminate bubbles in the solution;

[0058] S3, coating the vacuumized mixed solution on a substrate and curing it to obtain a ZIF-67 / PDMS composite film;

[0059] S4. Immerse the ZIF-67 / PDMS composite film in a fluorosilane solution and dry it to obtain a F-ZIF-67 / PDMS composite film.

[0060] In some embodiments, the fluorosilane solution includes perfluorodecyltrimethoxysilane and ethanol, and the mass concentration of perfluorodecyltrimethoxysilane in the fluorosilane solution is 1-2%.

[0061] In some embodiments, the method for preparing ZIF-67 powder comprises the following steps:

[0062] Dissolve Co(NO3)2 in methanol, then add a methanol solution containing 2-methylimidazole to obtain a mixed solution;

[0063] The mixed solution was stirred, aged, and centrifuged to obtain a precipitate, which was then washed and dried to obtain ZIF-67 powder.

[0064] In some embodiments, the ultrasonic dispersion time is 30 to 100 min;

[0065] In some embodiments, the mass ratio of the curing agent to the PDMS substrate is 1:(10-12).

[0066] In some embodiments, the mass ratio of ZIF-67 powder to PDMS precursor is 1:(10-100).

[0067] In some embodiments, the curing time is 1 to 4 hours, and the curing temperature is 70 to 90°C.

[0068] In some embodiments, in the step of immersing the ZIF-67 / PDMS composite film in a fluorosilane solution, the immersion temperature is 20-25° C. and the immersion time is 2-3 h.

[0069] In some embodiments, the mixed solution is stirred for 2 to 4 hours, aged, and centrifuged to obtain a precipitate, which is then centrifuged and washed with methanol and dried to obtain ZIF-67 powder; wherein the aging temperature is 20 to 25°C, the aging time is 20 to 30 hours, the centrifugal speed is 1000 to 1200 rpm, and the centrifugal time is 1 to 2 minutes.

[0070] In some embodiments, the mass volume ratio of Co(NO3)2, methanol, and a methanol solution containing 2-methylimidazole is (3-4) g: (40-50) mL: (80-100) mL.

[0071] In some embodiments, the mass of 2-methylimidazole in the methanol solution containing 2-methylimidazole is 3.5-4.0 g.

[0072] In some embodiments, the substrate is a glass substrate.

[0073] The present invention can prepare a high-performance F-ZIF-67 / PDMS composite film through simple steps such as solution mixing, stirring, curing, and soaking; this preparation method has the advantages of low cost, simple operation, good repeatability, etc., and is conducive to large-scale production and commercial application; ZIF-67, as a metal organic framework (MOF) material, has a rich pore structure and a high specific surface area, and compounding it with PDMS can significantly improve the triboelectric performance and charge storage capacity of the film; PDMS itself has good flexibility, biocompatibility and chemical stability, and can be further combined with ZIF-67 to The mechanical strength and durability of the material are enhanced; the metal organic framework is embedded in PDMS to improve the dielectric constant, and the chemical properties of the material surface are significantly changed after the ZIF-67 / PDMS film is fluorinated, especially the electronegativity of the material is improved and the surface energy is reduced; and PTFE material with a large difference in electronegativity is selected as the positive friction material, which greatly increases the number of charges between the friction materials, achieves higher power generation efficiency and more stable output performance, and TENG can also effectively convert mechanical energy into electrical energy, providing a stable and reliable energy supply for low-power electronic devices.

[0074] Based on the same inventive concept, the present invention also provides a F-ZIF-67 / PDMS composite film, which is prepared by the above-mentioned preparation method.

[0075] Based on the same inventive concept, the present invention also provides an application of the above-mentioned F-ZIF-67 / PDMS composite film as a positive friction material in the preparation of a friction nanogenerator.

[0076] Based on the same inventive concept, the present invention also provides a friction nanogenerator, comprising a first power generation unit and a second power generation unit;

[0077] The first power generation unit includes a first electrode and a negative friction layer located on the surface of the first electrode;

[0078] The second power generation unit includes a second electrode and a positive friction layer located on the surface of the second electrode;

[0079] Wherein, the negative friction layer material is the above-mentioned F-ZIF-67 / PDMS composite film;

[0080] The first electrode is electrically connected to the second electrode.

[0081] The friction nanogenerator of the present invention is composed of key components such as a positive friction layer, a negative friction layer, electrodes and wires. Among them, the negative friction layer specifically adopts a mixed material of fluorinated ZIF-67 and PDMS, that is, F-ZIF-67 / PDMS composite film, while the positive friction layer uses PTFE material with a significant difference in electronegativity from F-ZIF-67 / PDMS; by introducing ZIF-67 nanoparticles, the dielectric constant of the composite film is significantly improved, and the composite film is fluorinated to affect the friction polarity of the dielectric layer, thereby improving the charge density and output performance of the friction nanogenerator. The friction nanogenerator of the present invention can efficiently convert mechanical energy in the environment into electrical energy, and has been successfully applied to electrochemical cathodic protection systems, which have shown excellent anti-corrosion effects on steels such as Q235 carbon steel, 304SS, and A3 carbon steel, bringing new solutions to the field of corrosion protection.

[0082] In some embodiments, further comprising a first substrate and a second substrate;

[0083] The first substrate is attached to the surface of the first electrode away from the negative friction layer;

[0084] The second substrate is attached to the surface of the second electrode away from the positive friction layer;

[0085] The material of the positive friction layer is PTFE (polytetrafluoroethylene).

[0086] In some embodiments, the F-ZIF-67 / PDMS composite film is coated on the first electrode as a negative friction material to form a first power generation unit; and PTFE is pasted on the second electrode as a positive friction material to form a second power generation unit.

[0087] In some embodiments, the external circuit is connected to the first electrode and the second electrode through a wire.

[0088] In some embodiments, the first electrode and the second electrode are made of materials with good electrical conductivity, such as copper foil, aluminum foil, graphite, etc.; the first substrate and the second substrate are made of acrylic plate or any other material with certain mechanical strength.

[0089] In some embodiments, the first substrate and the second substrate are both 4×4×0.5 cm 3 The acrylic plate (i.e., a length of 4 cm, a width of 4 cm, and a height of 0.5 cm), the length of the first electrode and the second electrode are 4 cm, a width of 4 cm, and a thickness of 200 μm, and the length of the negative friction layer and the positive friction layer are 4 cm, a width of 4 cm, and a thickness of 200 μm.

[0090] Further, such as Figure 1As shown, it shows a schematic diagram of the structure of the friction nanogenerator of the present invention; the friction nanogenerator includes: a first power generation unit and a second power generation unit, the first power generation unit includes a first substrate 16, a first electrode 15, and a negative friction layer 14 that are sequentially bonded, and the second power generation unit includes a second substrate 13, a second electrode 12, and a positive friction layer 11; the negative friction layer 14 is a F-ZIF-67 / PDMS composite film, and the positive friction layer 11 is PTFE; the first electrode 15 and the second electrode 12 are connected to a load (Load) 17 by a wire.

[0091] Specifically, refer to Figure 2 As shown, it shows the principle of the friction nanogenerator of the present invention (the first electrode and the second electrode of the friction nanogenerator are both Cu): in the initial stage, the negative friction layer and the positive friction layer will not be electrified before contact; when they rub against each other for the first time, equal amounts of opposite charges are generated on the surface of the F-ZIF-67 / PDMS composite film and PTFE. The F-ZIF-67 / PDMS composite film is negatively charged because it is easier to obtain electrons than PTFE. When the two electrodes are separated from each other, the potential difference between the two electrodes drives electrons from the first electrode to the second electrode until the potential reaches equilibrium. Under the action of pressure, the two are close again. At the same time, the equilibrium potential is broken again, driving electrons from the second electrode to the first electrode. When they are separated and contacted, the current formed is in the opposite direction. Therefore, the friction generator generates periodic alternating current when it is repeatedly separated and contacted.

[0092] Based on the same inventive concept, the present invention also provides an application of the above-mentioned friction nanogenerator in electrochemical cathodic protection, self-powered sensors and wearable devices.

[0093] The friction nanogenerator of the present invention has the advantages of high output efficiency and simple preparation process, which makes the friction nanogenerator of the present invention have broad application prospects and important social significance in the fields of self-powered anti-corrosion, energy collection, environmental monitoring, etc.

[0094] The following further describes the F-ZIF-67 / PDMS composite film and its preparation method and application, friction nanogenerator and application of the present application with specific examples. This section further describes the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0095] In the following embodiments, the PDMS precursor includes a curing agent and a PDMS matrix, specifically Dow Corning SYLGARD 184 silicone rubber, and the curing agent and the PDMS matrix are mixed in a mass ratio of 1:10.

[0096] Example 1

[0097] The present invention provides a method for preparing ZIF-67 powder, comprising the following steps:

[0098] S1, 3.3 g of Co(NO3)2·6H2O were dissolved in 45 mL of methanol, and then 90 mL of methanol solution containing 3.7 g of 2-methylimidazole was added and mixed to obtain a mixed solution;

[0099] S2. The mixed solution in S1 was magnetically stirred for 2 h and then placed in an aging box for aging at room temperature (25°C) for 24 h. The obtained purple precipitate was centrifugally washed 6 times with methanol and dried in a vacuum oven at 60°C overnight to obtain ZIF-67 powder.

[0100] Figure 3 is the SEM image of the ZIF-67 powder prepared in Example 1; Figure 3 It can be seen that the ZIF-67 powder presents many smooth, randomly oriented polyhedrons or rhombic dodecahedron morphologies, and the synthesized ZIF-67 particle sizes range from 400nm to 500nm with a small amount of agglomeration.

[0101] Example 2

[0102] This embodiment provides a method for preparing a F-ZIF-67 / PDMS composite film, comprising the following steps:

[0103] S1. Add ZIF-67 powder to PDMS precursor, stir and then disperse by ultrasonic for 30 minutes to obtain a mixed solution; the PDMS precursor includes a curing agent and a PDMS matrix; the mass ratio of the curing agent to the PDMS matrix is ​​1:10; the mass fraction of ZIF-67 powder in the mixed solution is 5wt%; the preparation method of ZIF-67 powder is the same as that in Example 1;

[0104] S2, vacuuming the mixed solution to eliminate bubbles in the solution;

[0105] S3, coating the vacuumed mixed solution on a glass substrate with a doctor blade, and transferring it to an oven at 80° C. for curing for 2 h, to form a 200 μm thick ZIF-67 / PDMS composite film on the surface of the glass substrate;

[0106] S4. Immerse the ZIF-67 / PDMS composite film in a fluorosilane solution at room temperature (25°C) for 2 hours and dry it to obtain a F-ZIF-67 / PDMS composite film; the fluorosilane solution includes perfluorodecyltrimethoxysilane and ethanol, and the mass concentration of perfluorodecyltrimethoxysilane in the fluorosilane solution is 1wt%.

[0107] Figure 4 This is the SEM image of the F-ZIF-67 / PDMS composite film prepared in Example 2.

[0108] from Figure 4 It can be seen that ZIF-67 nanoparticles can be evenly distributed in PDMS and tightly adhere to PDMS, thus ensuring the high performance and durability of the device.

[0109] Figure 5 XRD patterns of the ZIF-67 powder in Example 2, pure PDMS (i.e., the curing agent and the PDMS matrix are mixed in a mass ratio of 1:10 and then cured to obtain pure PDMS), the F-ZIF-67 / PDMS composite film prepared in Example 2, and the ZIF-67 / PDMS composite film prepared in step S3 of Example 2.

[0110] from Figure 5 It can be seen that the addition of ZIF-67 destroys the crystal structure of PDMS compared with ZIF-67 alone and ZIF-67 / PDMS; in addition, ZIF-67 / PDMS has obvious diffraction peaks at 2θ=7.31°, 12.72°, 18.04°, 26.7°, 29.67° and 31.55° corresponding to the crystal plane of ZIF-67, which indicates the success of bonding; however, for the F-ZIF-67 / PDMS composite film, its XRD pattern is similar to that of the ZIF-67 / PDMS composite film, and no significant crystal structure changes are observed, indicating that the fluorosilane treatment process does not change the overall crystal morphology of the composite material. Nevertheless, since the immersion treatment of the sample in the fluorosilane solution may have caused the shedding of some ZIF-67 powder or the reduction of its content, the characteristic diffraction peak intensity of ZIF-67 was relatively weakened in the corresponding XRD pattern. This observation further supports the potential effect of fluorosilane treatment on the ZIF-67 content in the ZIF-67 / PDMS composite material.

[0111] Example 3

[0112] This embodiment provides a triboelectric nanogenerator, comprising a first power generation unit and a second power generation unit;

[0113] The first power generation unit includes a first electrode and a negative friction layer located on the surface of the first electrode;

[0114] The second power generation unit includes a second electrode and a positive friction layer located on the surface of the second electrode;

[0115] Wherein, the negative friction layer material is the F-ZIF-67 / PDMS composite film prepared in Example 2;

[0116] The first electrode is electrically connected to the second electrode;

[0117] Also included is a first substrate and a second substrate;

[0118] The first substrate is attached to the surface of the first electrode away from the negative friction layer;

[0119] The second substrate is attached to the surface of the second electrode away from the positive friction layer;

[0120] The material of the positive friction layer is PTFE (polytetrafluoroethylene);

[0121] The first electrode and the second electrode are both copper foils;

[0122] The first and second substrates are both 4×4×0.5cm 3 The acrylic plate (i.e., a length of 4 cm, a width of 4 cm, and a height of 0.5 cm), the length of the first electrode and the second electrode are 4 cm, a width of 4 cm, and a thickness of 200 μm, and the length of the negative friction layer and the positive friction layer are 4 cm, a width of 4 cm, and a thickness of 200 μm.

[0123] Comparative Example 1

[0124] The friction nanogenerator provided in this comparative example is the same as that in Example 3, except that the negative friction layer material is the ZIF-67 / PDMS composite film prepared in step S3 of Example 2, and the rest is the same as that in Example 3.

[0125] Comparative Example 2

[0126] The friction nanogenerator provided in this comparative example is the same as that in Example 3, except that the negative friction layer material is pure PDMS (i.e., the curing agent and the PDMS matrix are mixed in a mass ratio of 1:10 and then cured to obtain pure PDMS), and the rest is the same as that in Example 3.

[0127] Figure 6 The triboelectric output performance of high-performance triboelectric nanogenerators based on pure PDMS, ZIF-67 / PDMS composite film, and F-ZIF-67 / PDMS composite film prepared according to the methods in Comparative Examples 1 to 2 and Example 3, respectively. Specifically, Figure 6In the figure, PDMS-PTFE represents a friction nanogenerator based on pure PDMS, ZIF-67 / PDMS-PTFE represents a friction nanogenerator based on ZIF-67 / PDMS composite film, and F-ZIF-67 / PDMS-PTFE represents a friction nanogenerator based on F-ZIF-67 / PDMS composite film.

[0128] Under the action of external force at a frequency of 3Hz, the positive friction layer and the negative friction layer achieved contact and separation. With the addition of ZIF-67, the output performance of TENG was improved and significantly enhanced. After the ZIF-67 / PDMS was fluorinated, the output performance of TENG reached the highest, and its voltage, current and charge reached 187.14V, 37.46μA and 72.54nC, respectively, which fully proved that the TENG has high-performance output characteristics. Therefore, the addition of ZIF-67 powder effectively improved the output performance of TENG, which is mainly because the addition of ZIF-67 particles increases the surface roughness of the PDMS composite film. This increased roughness helps to generate more effective contact area during the friction process, thereby increasing the transfer and accumulation of charges and improving the output performance of TENG. In addition, fluorination modification enhances the friction effect between PDMS and PTFE by changing the microstructure or chemical properties of the PDMS surface. This enhancement is due to the increase in the roughness of the PDMS surface after fluorination, or the enhanced interaction between fluorine atoms and fluorine atoms in PTFE.

[0129] Figure 7 The high-performance friction nanogenerator F-ZIF-67 / PDMS-TENG in Example 3 was connected to a rectifier bridge, which converted the alternating current (AC) generated by F-ZIF-67 / PDMS-TENG into direct current (DC), which was then introduced into external electronic components, easily lighting up 111 LED lights.

[0130] Due to its excellent output performance, the high-performance friction nanogenerator F-ZIF-67 / PDMS-TENG in Example 3 was used as a cathodic protection power source to construct a self-powered anti-corrosion system. Figure 8The self-powered anti-corrosion system based on F-ZIF-67 / PDMS-TENG is shown. Specifically, F-ZIF-67 / PDMS-TENG is connected to the rectifier bridge, the working electrode is Q235 carbon steel (connected to the negative electrode of the rectifier bridge), and the counter electrode is a platinum electrode (connected to the positive electrode of the rectifier bridge). The Q235 carbon steel and the platinum electrode are placed in a NaCl solution with a mass concentration of 3.5wt%. F-ZIF-67 / PDMS-TENG injects electrons into the carbon steel surface through the rectifier circuit to polarize the cathode and prevent metal corrosion. In a three-electrode system (the working electrode is Q235 carbon steel, the counter electrode is a platinum electrode, the reference electrode is a saturated calomel electrode (SCE), and the electrolyte is a NaCl aqueous solution with a mass concentration of 3.5%), the OCP changes of Q235 carbon steel with and without TENG alternating coupling are measured, as shown in FIG. Fig. 9 As shown in the figure, the potential of carbon steel is maintained at -1.02 V vs. SCE. When TENG is added to the system, the OCP value of carbon steel moves sharply to -1.3 V vs. SCE. When TENG is removed, the OCP returns to its original value. In metal corrosion tests, the greater the OCP decreases, the better the corrosion resistance. At the same time, the Tafel curve of carbon steel is also measured, and the results are shown in Fig.10 As shown in Figure 2, its potential is more negative than that without TENG protection, and the potential is reduced by about 150mV. This finding further proves the effectiveness of the self-powered anti-corrosion system and echoes the OCP reduction observed in previous tests. In addition, the self-powered anti-corrosion system composed of F-ZIF-67 / PDMS-TENG effectively prevents the corrosion of metals.

[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a F-ZIF-67 / PDMS composite film, characterized in that: The following steps are involved: Adding ZIF-67 powder to a PDMS precursor, stirring and then ultrasonically dispersing to obtain a mixed solution; the PDMS precursor includes a curing agent and a PDMS matrix; The mixed solution was vacuumed to eliminate air bubbles in the solution; The vacuumized mixed solution is coated on a substrate and cured to obtain a ZIF-67 / PDMS composite film; The ZIF-67 / PDMS composite film is immersed in a fluorosilane solution and dried to obtain a F-ZIF-67 / PDMS composite film.

2. The method for preparing the F-ZIF-67 / PDMS composite film according to claim 1, wherein The fluorosilane solution comprises perfluorodecyltrimethoxysilane and ethanol, and the mass concentration of perfluorodecyltrimethoxysilane in the fluorosilane solution is 1-2%.

3. The preparation method of F-ZIF-67 / PDMS composite film as claimed in claim 1, characterized in that, The preparation method of the ZIF-67 powder comprises the following steps: Dissolve Co(NO3)2 in methanol, then add a methanol solution containing 2-methylimidazole to obtain a mixed solution; The mixed solution was stirred, aged, and centrifuged to obtain a precipitate, which was then washed and dried to obtain ZIF-67 powder.

4. The preparation method of F-ZIF-67 / PDMS composite film as claimed in claim 1, characterized in that, The ultrasonic dispersion time is 30 to 100 minutes; And / or, the mass ratio of the curing agent to the PDMS substrate is 1:(10-12); And / or, the mass ratio of the ZIF-67 powder to the PDMS precursor is 1:(10-100); And / or, the curing time is 1 to 4 hours and the curing temperature is 70 to 90°C.

5. The method for preparing the F-ZIF-67 / PDMS composite film according to claim 1, wherein In the step of immersing the ZIF-67 / PDMS composite film in a fluorosilane solution, the immersion temperature is 20 to 25° C. and the time is 2 to 3 hours; And / or, stirring the mixture for 2 to 4 hours, aging, centrifuging to obtain a precipitate, washing it by centrifugation with methanol, and drying it to obtain ZIF-67 powder; wherein the aging temperature is 20 to 25° C., and the aging time is 20 to 30 hours; and / or, the mass volume ratio of Co(NO3)2, methanol, and methanol solution containing 2-methylimidazole is (3-4) g: (40-50) mL: (80-100) mL; The mass of 2-methylimidazole in the methanol solution containing 2-methylimidazole is 3.5-4.0 g.

6. A F-ZIF-67 / PDMS composite film, characterized in that The preparation is obtained by the preparation method according to any one of claims 1 to 5.

7. Use of the F-ZIF-67 / PDMS composite film as claimed in claim 6 as a positive friction material in the preparation of a friction nanogenerator.

8. A friction nanogenerator, characterized in that: comprising a first power generation unit and a second power generation unit; The first power generation unit includes a first electrode and a negative friction layer located on the surface of the first electrode; The second power generation unit includes a second electrode and a positive friction layer located on the surface of the second electrode; Wherein, the negative friction layer material is the F-ZIF-67 / PDMS composite film as claimed in claim 6; The first electrode is electrically connected to the second electrode.

9. The triboelectric nanogenerator according to claim 8, characterized in that: Also included is a first substrate and a second substrate; The first substrate is attached to the surface of the first electrode away from the negative friction layer; The second substrate is attached to the surface of the second electrode away from the positive friction layer; The material of the positive friction layer is PTFE.

10. Use of the triboelectric nanogenerator as claimed in any one of claims 8 to 9 in electrochemical cathodic protection, self-powered sensors and wearable devices.

Citation Information

Patent Citations

  • Personal energy managing device containing fluoroalkyl silane hydrophobic surface layer and production and application of personal energy managing device

    CN105603725A

  • PDMS@F-MOF composite film for friction nanometer generator and preparation method for PDMS@F-MOF composite film

    CN111087635A

  • Friction nano-generator

    CN111200376A

  • Preparation method of friction nanometer generator based on F-MXene

    CN116827164A

  • Nano-composite membrane based on fibroin and zeolite imidazole framework material as well as preparation method and application of nano-composite membrane

    CN116904037A